Outcomes of Liver Transplant Recipients With Autoimmune Liver Disease Using Long-Term Dual Immunosuppression Regimen Without Corticosteroid - Satapathy, Sanjaya K. (Transplant Direct, 2017)
BACKGROUND: Liver transplant (LT) recipients with autoimmune liver disease (primary sclerosing cholangitis, primary biliary cholangitis, autoimmune hepatitis) are at increased risk of developing acute cellular rejection (ACR), and in many cases graft failure due to recurrent disease. We describe our experience with dual immunosuppression without steroid maintenance and analyze its effect on disease recurrence; ACR; patient and graft survivals; and complications, such as sepsis and de novo malignancy. METHODS: We included 74 consecutive LT recipients (April 2006 to April 2013) with autoimmune liver disease (primary sclerosing cholangitis, 20; primary biliary cholangitis, 23; autoimmune hepatitis, 31) from a single transplant center. Immunosuppression protocol included rabbit antithymocyte globulin for induction and mycophenolate mofetil with tacrolimus or sirolimus/everolimus indefinitely for maintenance. RESULTS: Overall 1-, 3-, 5-, and 7-year patient survival was 95.9%, 90.4%, 82,2% and 74.9%, re–graft-free survival was 93.2%, 86.3%, 79.9%, and 72.8%, respectively (median follow-up, 5.5 years). In a multivariate Cox regression analysis, sepsis during post-LT period (P = 0.040; hazard ratio [HR], 2.52; 95% confidence interval [CI], 1.04-6.11), steroid use for ACR (P = 0.037; HR, 2.60; 95% CI, 1.06-6.34), and younger age (<40 years) at LT (P = 0.038; HR, 2.53; 95% CI, 1.05-6.10) predicted graft survival, whereas steroid use for ACR was the only variable that was predictive of overall patient survival (P = 0.004; HR, 4.10; 95% CI, 1.59-10.52). Overall, 34 biopsy-proven ACR was noted in 22 LT recipients (30%), 13 (17.5%) had disease recurrence, and 34 episodes of sepsis occurred in 19 patients. CONCLUSIONS: Dual immunosuppression protocol in LT recipients with autoimmune liver disease without corticosteroid maintenance had acceptable rates of survival and ACR without predisposing patients to the adverse effects of long-term steroid therapy.